Expression of Sexuality and Cultural Symbols in Guritan "Gisik Banyuwangi" by Tayib Muryanto - `Fuadhiyah, Ucik; Purwasito, Andrik; Abdullah Rais, Wakit; Supriyanto, Teguh (Proceeding of International Joint Conference on UNESA, 2025)
The approach used in this research is qualitative. Theoretically, this research uses a semiotic approach. The semiotics referred to refers to the concept of Roland Barthes, where this approach is considered relevant to the research objective, namely to reveal the meaning of both the denotation level, the connotation level, and the myths that are built. Based on the results of the analysis of the dictions in the text of the guritan "Gisik Banyuwangi" revealed, among others: 1) In the gurit "Gisik Banyuwangi" by Tayib M, the part that shows the image of sexuality, for example, is found in the lines that read: kacathet ing telenging ati; temanten during salaki rabi; dhuh polahe kenya kelangan tresna; wis kokrungu kidung suci; ngresah; ah, kabeh kakehan polah. If we examine the story narrated in the geguritan "Gisik Banyuwangi". 2) All activities and elements present in sexual activity are an effort to achieve awareness of the process of creation. With this awareness, humans will appreciate, respect, and maintain the sanctity of each process. Likewise, the concept of sexuality as a precursor to spirituality is expected to lead humans to be more grateful for and preserve what nature and the Creator have provided. It should not be used merely as a means of satisfying lus